One step nanoencapsulation of corrosion inhibitors for gradual release application. (June 2022) - Privitera, A.; Ruggiero, L.; Venditti, I.; Pasqual Laverdura, U.; Tuti, S.; De Felicis, D.; Lo Mastro, S.; Duranti, L.; Di Bartolomeo, E.; Gasperi, T.; Ricci, M.A.; Sodo, A.
Abstract: The direct application of corrosion inhibitors on metal surfaces is potentially dangerous for the environment and the restoration operators, thus new conservation strategies are mandatory. In this study, two copper corrosion inhibitors, 1H-benzotriazole (BTA) and 5-phenyl-1H-tetrazole (PT), are encapsulated in a silica nanocontainer, for future application in smart coatings, with the aim to reduce the amount of chemicals used in treatments, their dispersion in the environment and the direct exposure of the operators to these chemicals. In particular, composite silica nanocapsules, containing the corrosion inhibitors, are prepared via one-step synthesis, based on mini-emulsion polymerisation processes. The morphology, structure, and texture of these loaded silica nanocontainers are characterised by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and N2 physisorption (BET/BJH). Micro-Raman spectroscopy (RS) is performed to characterise the composition. UV–visible spectroscopy and thermal analysis (TG/DSC) are performed for the loading and encapsulation efficiency (L%, EE%) study. Synthesised nanocapsules show a core-shell structure and, when loaded with the inhibitors, have size ranging from about 130 to 170 nm and a BET surface area of the order of 800 m 2 /g. The EE% is maximum in the case of BTA and decreases to ∼52% in the case of PT. Graphical abstract: Image 1 Highlights: Design of nanocontainers loaded with corrosion inhibitors to reduce the toxicity. Encapsulation of corrosion inhibitors via one step self-assembly and sol–gel methods. Silica core-shell nanocapsules of nanometer size. Successful encapsulation of 1H-Benzotriazole and 5-phenyl-1H-tetrazole.